The Factors of Initial Return Related to IPO Companies on The Indonesia Stock Exchange - Glynae Widyawati; Bambang Juanda; Trias Andati (Journal of Consumer Sciences, 2019)
Companies that conduct IPOs will increase company’s value with an optimal capital structure. Initial return is a profit that investors can obtain from the initial share price is lower than the opening price of the secondary shares on the first day. Underpricing conditions occurs because the initial stock price is lower than the secondary stock price on the first day. This study aimed to analyze factors that impact initial returns on companies that conduct IPOs on the Indonesia Stock Exchange, analyze the effects of financial factors (ROE, DER, and BI Rate) and non-financial factors (professional auditors and underwriters) on initial returns to companies conducting IPOs in IDX, and how the behavior of investors towards those analysis. The linear regression data processing using SPSS 16 produced result that only the BI Rate variable which affected the initial return on the seven days, 30 days, and one year after the IPO observation period. The statistical results show the best r-square value is 17.6 percent, which means that the independent variables can be used to explain the effect to the initial return on 17.6 percent.